Networking a contemporary marketing strategy for generating extra income of people in Iloilo City - Abelarde, Valerie Joy; Bellescas, Ma. Fe; Caduada, Lorlyn; Cubar, Emily; Lunasco, Cyramae
This study sought to find out Networking as a contemporary marketing strategy for generating extra income of people in Iloilo City. The respondents of the study were distributors of the three (3 majors networking companies here in Iloilo City, which are Forever Living Products International, DXN Private Limited, and Empower Moreishi. Questionnaires on checklist form were used to gather the responses of distributors. The percentage nd frequency count were used as statistical tools in interpreting the data. The study revealed that indeed networking is a contemporary marketing strategynfor generating extra income of people in Iloilo City. These aspects were determined in terms of their socio-economic profile, the ways in which they could avail of the incentives and benefits offered by the company and their sales performance.